P067 Advancing IL-22-Based Therapies for Inflammatory Bowel Diseases With Human Intestinal Organoids. (December 2019) - Patnaude, Lori; Mayo, Martha; Mario, Regina; Wilson, Sarah; Knight, Heather; Karsen, Sam; Yang, Yingli; Melim, Terry; Creamer, Kelly; Pivorunas, Valerie; Westmoreland, Susan; Dunstan, Bob; et al.
Abstract : BACKGROUND: Inflammatory bowel diseases (IBD) are chronic inflammatory disorders of the gastro-intestinal tract for which the key elements in disease initiation and perpetuation are defects in epithelial barrier integrity and repair. Inducing and maintaining mucosal healing has the potential to address unmet medical need in IBD of achieving greater efficacy and more durable disease remission than current therapies. Recent studies suggest that IL-22 regulates epithelial homeostasis and promotes repair of epithelial damage, thus making IL-22 a promising target for IBD therapy. In an effort to better understand IL-22 biology we have used human colon organoids to strengthen our understanding of the mechanisms by which IL-22 regulates mucosal healing. METHODS: Human colon organoids derived from healthy and ulcerative colitis (UC) donor biopsies were cultured using a standard protocol and treated with recombinant IL-22 protein alone or in combination with microbial-derived metabolites at multiple concentrations and time points. Cell viability, organoid forming capacity, epithelial cell function, as well as gene expression analysis of markers of epithelial cell types and signaling pathways were then assessed. To recapitulate the inflammatory environments associated with IBD, organoids were also co-cultured with anti-CD3/CD28 activated T cells. In-vivo studies were also performed in naïve mice dosed with IL-22-Fc to evaluate the in-vitro/in-vivo translatability. RESULTS: IL-22 treatment led to stem cell survival, cell proliferation and production of anti-microbial peptides in organoids. IL-22 treatment also altered the mucus barrier by inducing an increase in membrane mucus but a decrease in both secreted mucus and goblet cell number. Interestingly, most of the IL-22 effects on the organoids were also observed in-vivo thus confirming the in vitro/in vivo translatability. In addition, IL-22 had the same inducing effect on anti-microbial peptides and the membrane mucus barrier in both healthy (n = 3) and UC (n = 3) organoids. In contrast, this IL-22-associated epithelial phenotype was different when organoids were co-cultured with activated T cells. Finally, IL-22 showed synergistic and additive effects with microbial-derived metabolites in inducing expression of antimicrobial peptides and membrane mucins. CONCLUSION(S): Our data indicate that IL-22 acts directly on the gut epithelium of both healthy and UC individuals to promote epithelial regeneration, innate defense and production of membrane mucus. In addition, our findings indicate that these IL-22 effects on epithelial cell function and mucosal healing mechanisms are differentially regulated in presence of either microbial-derived metabolites or activated T cells. Overall, this data strongly supports clinical relevance of IL-22 as a mucosal healing therapy in IBD and suggests that the efficacy may be impacted by microbial-derived metabolites and inflammatory environments.